EKSISTENSI HUKUM ADAT MELAYU LIMO KOTO DALAM PENERAPAN SANKSI TERHADAP PELAKU PENCURIAN KAYU RIMBA LARANGAN ADAT DI NAGARI RUMBIO - Khairul Bakri; Erdianto Effendi; Zulfikar Jayakusuma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The law always exists in every society. In the Limo Koto Kenegarian Region, Rumbio Jaya District, the community still uses their customary law in resolving criminal acts or crimes, especially crimes in the theft of jungle timber / customary forest prohibitions. The purpose of this thesis writer is: First, how is the application of sanctions against the perpetrators of illegal logging of forest timber in Nagari Limo Koto, Rumbio Jaya District. Second, what is the position and constraints of customary law on law enforcement and how is the practice in Nagari Limo Koto, Rumbio Jaya District. This type of research uses direct sociological research methods at the location or place to be studied. This research was conducted in Kanagarian Limo Koto, Rumbio Jaya District, Kampar Regency, Riau Province. While the population and sample are all parties related to the problems examined in this research, the data sources used are primary data, secondary data and tertiary data, the technique of data collection in this study is by interview and document study. Conclusion that the existence of the imposition of sanctions against perpetrators of illegal logging / forest prohibition of customary laws such as social sanctions and criminal fines in terms of practice in the field has begun to fade and the lack of supervision of the forest / jungle ban until now, people are still taking wood silently and stout motive or method used by the perpetrator. The writer's suggestion is for the nagari government and its instruments to increase the supervision of the forest / jungle of customary prohibitions and to make nagari regulations governing customary law or violation of customary law and to work with government authorities and the police and to socialize to the nagari Limo Koto community so that customary law is Malay Koto limo still exists and will not fade with the times Keywords: Existence - Customary Law - Theft of Nagari Forest / Forest